Multibeam bathymetry raw data (Kongsberg EM710 entire dataset) of RV METEOR during cruise M78/3B - Gerold Wefer; Federico Damián Esteban; Benedikt Preu (PANGAEA, 2022)
Multibeam bathymetry raw data using the ship extquotesingles own Kongsberg EM 710 multibeam echosounder was not continuously recorded during RV METEOR cruise M78/3B. Data was recorded only on 2 days between 2009-06-20 and 2009-07-05. This dataset contains a survey out of and towards the Río de la Plata. The data are archived at the Federal Maritime and Hydrographic Agency of Germany (Bundesamt für Seeschifffahrt und Hydrographie, BSH) and provided to PANGAEA database for data curation and publication. No ancillary sound velocity profiles (SVP) files from the cruise are archived at the BSH, thus no SVP files are added to this dataset. However, also data analysis of the multibeam raw data revealed that SVP has not been changed during the survey. This publication is conducted within the efforts of the German Marine Research Alliance in the core area extquotesingleData management and Digitalization extquotesingle (Deutsche Allianz Meeresforschung, DAM). Data are unprocessed and therefore contains incorrect depth measurements (artifacts) without further processing. Note that refraction errors can be expected due to the lack of proper SVP. Overall, it appears that the data quality of several survey line is rather poor since the gridded hillshade data showed relatively many obstacles. The swath width is occasionally very wide; therefore, the measurements are probably not realistic (these affected files are marked in the parameter table). Data can be processed e.g. with the open source software package MB-System (Caress, D. W., and D. N. Chayes, MB-System: Mapping the Seafloor, http://www.mbari.org/products/research-software/mb-system/, 2022).